(untitled) (XXI Century. Spanish Literature and Culture, 2015)
: In Luz de la memoria, Lourdes Ortiz uses her own life experience and current affairs to question the Transition process from its very origins. The author creates a kind of fictional alter ego, Enrique García Alonso. This young man who, like Lourdes Ortiz, was part of generation 68 and whose youth was strongly committed politically to the Marxist Leninist struggle. Giving her novel its place in 1976 at Madrid, Lourdes Ortiz provides testimony about the process that forecast the Transition arrival, which by the way, was not as promising and glorious as people could have said. In the novel, the difference between desires and reality, along with Enrique’s frustrated hopes, gives emphasis to the latest statement. As a result, the novelist creates to that purpose a fictional judgment between winners and losers in which injustice drives Enrique to a situation of personal crisis. For him, suicide and drugs are then the only way-out.